The telomere binding protein Pot1 maintains haematopoietic stem cell activity with age - Kentaro Hosokawa (Nature Portfolio, 2017)
Repeated cell divisions induce DNA damage in haematopoietic stem cells (HSC) and telomeres are sensitive to this damage. Here, the authors show in murine HSCs that the telomere binding protein POT1a inhibited the production of reactive oxygen species, and rejuvenated aged HSCs.